1996
DOI: 10.1080/13102818.1996.10818904
|View full text |Cite
|
Sign up to set email alerts
|

On Some Aspects of a New Fermented Milk Product Medina

Abstract: Honey as a valuable biological food has had a lasting presence in human diet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 1 publication
1
12
1
Order By: Relevance
“…After 6 wk of storage, viability retention of lactobacilli in the final products ranged between 36.3% and 42.3%. These results are in contrast to those of Roumyan et al (1996), who found a considerable inhibition in the growth of L. bulgaricus when testing the influence of honey addition on the starter organisms in Bulgarian yogurt.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…After 6 wk of storage, viability retention of lactobacilli in the final products ranged between 36.3% and 42.3%. These results are in contrast to those of Roumyan et al (1996), who found a considerable inhibition in the growth of L. bulgaricus when testing the influence of honey addition on the starter organisms in Bulgarian yogurt.…”
Section: Resultscontrasting
confidence: 55%
“…Nevertheless, honey-yogurt combinations are relatively uncommon (Brown and Kosikowski, 1970;Roumyan et al, 1996). A plausible explanation for this is that honey is known to have inhibitory effects on lactic starter cultures (Čurda and Plocková, 1995;Roumyan et al, 1996). Factors in honey contributing to its antibacterial nature have clearly not been fully understood (Taormina et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have reported the inhibitory effects of honey against lactic acid bacteria (LAB;urda and Plocková, 1995;Roumyan et al, 1996), which are due to the high sugar concentration, relatively high acidity, and presence of both organic acids and low concentrations of hydrogen peroxide (Roumyan et al, 1996;Mundo et al, 2004). Recently, other authors (Sanz et al, 2005;Ezz El-Arab et al, 2006) showed that, when used at suitable levels, honey does not inhibit the growth of common bacteria, and could be used as a sweetener and a useful preservative agent in dairy products (Chick et al, 2001;Varga, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Sucrose and corn syrup have been the traditional and most commonly used sweeteners in the dairy industry. Although honey has been added as a flavouring agent in fermented dairy products, honey yoghurt combinations are relatively uncommon (Brown and Kosikowski 1970; Roumyan et al. 1996).…”
Section: Introductionmentioning
confidence: 99%